Identification of Students' Misconceptions in Static Fluid - Alfad, Haritsah (Tarbiyah : Jurnal Ilmiah Kependidikan, 2020)
This study aimed to identify students’ misconceptions in static fluid covering Archimedes’ Principle and hydrostatic pressure. The used-instruments were of 10 multiple choice questions supported by reasons for answers. The method used in this research was giving the exercise in the form of questions to 32 students of XI class who had received subject matter of Archimedes’ Principle and hydrostatic pressure at middle and high school levels. The results of the students’ answers were then analyzed and presented qualitatively and quantitatively. Based on the analysis of students’ answers obtained 16 types of misconceptions in static fluid. In comprehending Archimedes' Principle, most students experienced difficulties in determining the state of floating, sinking and determining magnitude of buoyancy of objects in a fluid. While on hydrostatic pressure topic, most students found it difficult to determine the amount of hydrostatic pressure at a point in the fluid.